A Comparative Case Study of Engineers' Literacy Practices and Implications for Transformative Disciplinary Literacy Pedagogies in Engineering Education. Issue 4 (9th August 2022) - Wilson‐Lopez, Amy; Minichiello, Angela; Green, Theresa; Hartman, Christina; Garlick, Jared
ABSTRACT: The purpose of this comparative case study, conducted with eight engineers in different firms who specialized in different disciplines of engineering, was to identify and describe the patterned ways in which they used written genres in the context of object‐oriented activity, as well as to describe their evaluative frameworks and literacy practices. The research team used descriptive coding to analyze field notes from twelve two‐hour observations per engineer; they also used categorical thematic analysis to analyze transcripts from six interviews and retrospective protocols per engineer. The analyses indicated that, to some extent, engineers read and wrote distinct written genres that varied according to their role (e.g., quality assurance manager versus test designer) and the traditions of their discipline (e.g., electrical versus mechanical). However, across sites, roles, and disciplines, they used common evaluative frameworks when they evaluated texts' accuracy, consistency, adherence to standards, currency, executability, reproducibility, concision, and clarity. In conjunction with these evaluative frameworks, engineers also enacted common literacy practices, such as cross‐checking, peer review, using templates when composing, and verifying with the physical world. The study concludes with implications for transformative, rather than reproductive, disciplinary literacy pedagogies in which students can use expansive disciplinary literacies in engineering to address issues that are important to them. As part of these pedagogies, students can articulate why common evaluative frameworks and literacy practices are important to producing safe outcomes in engineering, while they simultaneously expand these frameworks and practices to reflect values and cultures that are important to them. Abstract : The purpose of this comparative case study, conducted with eight engineers in different firms who specialized in different disciplines of engineering, was to identify and describe the patterned ways in which they used written genres in the context of object‐oriented activity, as well as to describe their evaluative frameworks and literacy practices.